If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -8) + -5(x + 6) = 2 Reorder the terms: 2(-8 + x) + -5(x + 6) = 2 (-8 * 2 + x * 2) + -5(x + 6) = 2 (-16 + 2x) + -5(x + 6) = 2 Reorder the terms: -16 + 2x + -5(6 + x) = 2 -16 + 2x + (6 * -5 + x * -5) = 2 -16 + 2x + (-30 + -5x) = 2 Reorder the terms: -16 + -30 + 2x + -5x = 2 Combine like terms: -16 + -30 = -46 -46 + 2x + -5x = 2 Combine like terms: 2x + -5x = -3x -46 + -3x = 2 Solving -46 + -3x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '46' to each side of the equation. -46 + 46 + -3x = 2 + 46 Combine like terms: -46 + 46 = 0 0 + -3x = 2 + 46 -3x = 2 + 46 Combine like terms: 2 + 46 = 48 -3x = 48 Divide each side by '-3'. x = -16 Simplifying x = -16
| -3x+21=6x-10 | | 4a-3b+2c= | | 100=4r | | M+(-19)=40 | | 6x+6=9x-6 | | (ab+4a+-6)+(ab+6)= | | 7(b+2)-13b=2(b-1)+6 | | 585.00+0.13x=525.00+0.21x | | x^2-2x+y^2-2y-3=0 | | X^3+7x-x-7=0 | | 2x-6=2(2-8)+10 | | 2x+6=y+4 | | 2x^2+-4x=0 | | 525.00+0.21x=585 | | 3x-2(5y-6)=8 | | 10(z+3)=5(z-8) | | 5-(x+3)=10 | | -t+15=2 | | 3u+147=180 | | x(x+1)=1024 | | x=15+7x-81 | | -7+3+-5= | | 6x-19=10x-79 | | 10m=(3m-11)-17 | | -2x^3+19X^2-38x+21=0 | | z=2z-68 | | 3x-11=2(x-3)-8 | | -26+17= | | 1=-3xy | | 4t+5=2 | | 3(1-2x)=6-6x | | 16+-12+-7= |